Higher-order Mode Rectangular Dielectric Resonator Antenna for 5G Applications - Nor Hidayu Shahadan; Muhammad Ramlee Kamarudin; Mohd Haizal Jamaluddin; Yoshihide Yamada (Institute of Advanced Engineering and Science, 2017)
The excitation of the higher-order mode, in rectangular dielectric resonator designed was explored to enhance the antenna gain and detailed elaboration is presented in this paper. The antenna was fed by a 50Ω microstrip line through an aperture cut in the ground plane. Besides avoiding spurious radiation, this feeding technique gives flexibility in controlling the amount of coupling in order to reduce the Q-factor in the higher-order mode RDRA. A design was developed and subsequently simulated using Ansoft HFSS ver 16.0 by utilizing Duroid 5880 dielectric substrate with a thickness (ts) of 0.254 mm, a permittivity (εs) of 2.2 and a loss tangent (δ) of 0.001 at 15 GHz. The higher-order mode, RDRA achieved the measured gain at 9.76 dBi and the measured impedance bandwidth as much 2.5 GHz which is 4.7% more compared to the fundamental mode. The result should be considered suitable for 5G applications.